Comparation of n-Heksan and Etanol in Bawang Dayak (Elutherine palmifolia L. Merr) Extraction for Inhibiting Pseudomonas aeruginosa: Penggunaan n-Heksan dan Etanol dalam Ekstraksi Bawang Dayak (Elutherine palmifolia L. Merr) Terhadap Kemampuan Daya Hambat Pseudomonas aeruginosa - Putri, Ananda Ghufron Yuana; Prayekti, Endah (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Pseudomonas aeruginosa is one of the bacteria that causes nosocomial infections. The incidence of nosocomial infections caused by Pseudomonas aeruginosa is around 10-15%. Nosocomial infections caused by these bacteria are increasingly difficult to treat. This happens because more and more strains are resistant to several antibiotics (Multidrug Resistance), so the selection of antibiotics against Pseudomonas aeruginosa is very difficult. This study aims to determine and analyze the effect of using polar and nonpolar solvents on Dayak onion bulb extract on the inhibitory ability of Pseudomonas aeruginosa. The method used in this study was Kirby-Bauer disk diffusion using 8 sample and 5 replication with assay solvent 96% ethanol and n-hexane extract of Dayak onion bulbs (Eleutherine palmifolia L. Merr) with concentration variations of 75%, 80%, and 85%. Positive control used ciprofloxacin 5 µg and positive control DMSO 10%. The results showed that on phytochemical screening of solvent ethanol 96% contained flavonoids and n-hexane contained triterpenoids. Ethanol 96% solvent obtained a higher presentase yield than n-heksan solvents and the highest inhibition zone diameter was 85% concentration in 96% ethanol solvent. The results of statistical analysis with Mann Whitney test showed a significant difference between the treatment groups (p<0.05).